BHDL: A Lucid, Expressive, and Embedded Programming Language and System for PCB Designs - Li, Hebi; He, Youbiao; Xiao, Qi; Tian, Jin; Bao, Forrest Sheng (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Graphical PCB design tools like KiCAD lack support for high-level abstraction such as functions and loops. To improve PCB design productivity, we hereby present BHDL, a programming framework for PCB designs. In its compact and declarative syntax, schematics and layouts can be modeled effectively and expressed concisely. Treating all circuits, even a resistor, as functions, BHDL naturally supports modularized development that builds a complex design up from smaller designs hierarchically. As an embedded Domain Specific Language (eDSL), BHDL allows users to leverage the full feature of the host language for customization and extension. Our Jupyter kernel supports web-based, REPL-style development and generates auto-placed PCBs.